Providing Core Curriculum Model for Second Grade of High School (European Journal of Behavioral Sciences, 2018)
This study is going to present a theoretical model for developing the core curriculum. The present study was conducted in an analytical descriptive method. The statistical population of the study consisted of experts and experts in the study including 200 experts and experts in the literature. a questionnaire was set in 80 questions from a Likert scale, the reliability of the questionnaire was estimated at 93 / 99. in order to evaluate the validity of the questionnaire, the questionnaire was used after the sampling adequacy ( KMO ) and the Bartlett test. to analyze the data from descriptive and inferential statistics, conceptualization process, factor analysis ( principal component analysis ) and path analysis were used. the results showed that the core curriculum is modeled in six factors. In the final step, using factor rotation, the simple structure of factors was obtained and factors under the titles of learning, content, and materials, organization of learning opportunity, design strategies and program implementation, learning strategies, program execution quality were named and the conceptual model was designed according to these six factors. And the statistics of path analysis in the form of a model showed that each of the six factors had sufficient importance to the core curricula.